Respon Pertumbuhan dan Produksi Sorgum (Sorghum bicolor (L.) Moench) terhadap Dosis dan Waktu Aplikasi Pupuk Silika - Martha Uli Sitorus; Rosita Sipayung; Jonatan Ginting (Jurnal Agroekoteknologi, 2019)
This study aims to obtain the silica fertilizer dosage and application time for growth and production sorghum (Sorghum bicolor (L) Moench.). This research was conducted at Faculty of Agriculture Universitas Sumatera Utara began from March until August 2018, This research used factorial randomized block design with two factors. The first factor was silica fertilizer dosage with four levels are 0 , 0.5, 1, and 1.5 gram/plot and the second factor was application time with four application time are: 10, 20, 30, and 40 Day After Planting. Parameter observed were plant's length, stem diameter, weight of 1000 seeds, weight of seed per sample and weight of seed per plot. Silica fertilizer and application time can improve growth and production of  sorgum variety Super 2. The highest production percentage of sorgum reach 55.27%  compared with control, the production reach 4.30 tons/hectare.